ANALISIS SIKAP NASIONALISME MAHASISWA PPKN UNIVERSITAS NEGERI MEDAN DALAM MEREALISASIKAN HAK ASASI WARGA NEGARA DI ERA REVOLUSI INDUSTRI 4.0 - Sinambela, San Mikael; Leryaldo Sinaga, Manotar; Defliyanti Saragih, Mima; Manullang, Jojor Mindo; Sihite, Irawati; Yunita, Sri (Inspiratif Pendidikan, 2023)
The era of the industrial revolution 4.0 demands the readiness of all stakeholders to be able to face very rapid growth and development. It is inevitable that growth is interpreted as a positive or negative result. The positive consequences are technological advances, revolutions in the industrial sector, as well as more and more technological innovations. The negative consequences of this growth is that it has a significant influence on changes in values, behavior, a spirit of nationalism, guarantess for the protection of the rights of domestic people. Therefore, this situation requires all parties to increase understanding, improve the attitude and spirit of nationalism, comitment and guarantess of human rights, both civil rights, political, economic, social, cultural, and development values. In addition, the need for strengthening learning institutios in order to form a personality in accomodating this.